Improvement of optical systems for detection of smokes; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Panin V. F. Vladimir Filippovich (2015, 2015)
Title screen